Localized surface plasmon enhanced carbon dots based solar-blind ultraviolet photodetectors by Al nanoparticles - Chen, Xinyue; Zhao, Zhiwei; Jia, Xi; Yu, Yanling; Fang, Yong; Zhu, Mengru; Weng, Zhengjin; Lei, Wei; Shafe, Suhaidi; Mohtar, Mohd Nazim (Society of Photo-optical Instrumentation Engineers, 2023)
Localized surface plasmon resonance (LSPR) can enhance the optical field density around the nanostructure to improve devices’ light absorption. Aluminum nanoparticles (Al NPs) were introduced into solar-blind photodetectors with carbon dots (CDs) as a photosensitive material. It is found that by inserting Al NPs into the device, the switching ratio, responsivity, and external quantum efficiency reached 125.9, 0.511 A/W, and 2.16, respectively, which has obvious improvement compared with CDs based photodetector. The results indicate that Al NPs have an apparent optimization effect on the performance of the CDs photodetector by stimulating LSPR, which improves the photoresponse ability of CDs. It is illustrated by finite difference time-domain method that Al NPs can constraint the light field energy and successfully stimulate LSPR.